GENDER ASPECTS OF THE EMPLOYER VALUE PROPOSITION FORMATION ON THE LABOR MARKET - SAMOLIUK, NATALIA; MISHCHUK, HALYNA; MISHCHUK, VIKTORIIA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
In modern conditions, the brand of the employer becomes a tool for differentiation of the company in the labour market, which allows achieving the competitive advantages in the rivalry for skilled workers. The need to develop the employer value proposition focused on the requirements and preferences of different target groups in order to strengthen the brand and increase the attractiveness of the company in the labour market is argued in the article. The priority of the components of the employer brand regarding gender differences is determined due to the survey conducted by the authors. It is proved that the expectations of representatives of different target groups regarding the HR brand may differ due to difference in age, gender, education, culture, employment status. Therefore, forming an HR-brand it is important to understand that it is impossible to attract any employee with one value proposition, i.e. EVP must be special in accordance with the expectations of each target segment. Particularly, the results of our study showed gender differences in perception of the importance of the criteria for selecting a potential job. For example, women prioritize career opportunities and a secure work environment, while men prioritize a company's reputation in the labour market and personal development opportunities. Employer value proposition must be a real embodiment of the benefits offered by the company to the employee; otherwise, it will be impossible to retain the employees involved and maintain their loyalty to the company. It is proved that the relevant value proposition is one of the strategic directions of the company's activity on attracting new and retaining existing employees.  Prospects for further research in this area are to improve the mechanism of formation and development of HR-brand, taking into account the value propositions of the employer for different (internal and external) target groups in crisis situations.
Keywords: labor market; employer; employee; employer brand; HR brand; employer's value proposition